ANUGA SOFTWARE FOR NUMERICAL SIMULATIONS OF SHALLOW WATER FLOWS - Sudi Mungkasi; Stephen Gwyn Roberts (Jurnal Ilmu Komputer dan Informasi, 2012)
Shallow water flows are governed by the shallow water wave equations, also known as the Saint-Venant system. This paper presents a finite volume method used to solve the two-dimensional shallow water wave equations and how the finite volume method is implemented in ANUGA software. This finite volume method is the numerical method underlying the software. ANUGA is open source software developed by Australian National University (ANU) and Geoscience Australia (GA). This software uses the finite volume method with triangular domain discretisation for the computation. Four test cases are considered in order to evaluate the performance of the software. Overall, ANUGA is a robust software to simulate two-dimensional shallow water flows. Arus air dangkal diatur dalam persamaan gelombang air dangkal, dikenal sebagai sistem Saint-Venant. Penelitian ini menyajikan metode finite volumeyang digunakan untuk menyelesaikan persamaan gelombang air dangkal dua dimensi dan bagaimana metode finite volumediimplementasikan dalam perangkat lunak ANUGA. Metode finite volumeadalah metode numerik yang mendasari perangkat lunakANUGA. ANUGA sendiri adalah perangkat lunak open source yang dikembangkan oleh Australian National University(ANU) dan Geoscience Australia (GA). Perangkat lunak ini menggunakan metode finite volumedengan diskritisasi domain segitiga dalam proseskomputasi. Empat uji kasus digunakan untuk mengevaluasi kinerja perangkat lunak. Secara keseluruhan, ANUGA adalah perangkat lunak yang robust untuk mensimulasikan dua dimensi aliran arus air dangkal.